2018
DOI: 10.18805/ag.d-4492
|View full text |Cite
|
Sign up to set email alerts
|

Variability Studies of strains of Kagzi lime(Citrus aurantifolia Swingle) in Latur district of Maharashtra

Abstract: The survey work was under taken to study the variability in kagzi lime of Latur district during 2010-2011. The strain LTR 5 recorded the maximum height of plant (4.22 m), which was on par with LTR 8 (4.20 m) and LTR 13 (4.18 m). There was a significant variation in tree volume ranged from 8.87 m 3 to 57.82 m. 3 The strain LTR 19 was recorded the maximum tree volume (57.82 m 3 ). Maximum number of fruits per tree (2390.00) was recorded in strain LTR 5 . Maximum fruit weight was recorded in LTR 11 (65.33 g), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Pule sharbatti, Balaji, Sai sharbatti varieties were round in shape whereas Kagzi lime, Vikram, Pramalini varieties were in oval shape. Similar observations were made by Yadlod et al (2018) [12] who noticed oval and round shaped fruits with rough and smooth surface fruits. The length of acid lime fruits was ranging from 4.15cm to 4.64 cm, these findings were in the range of observations were made by Tirthakar et al (2004) [11] ranging between 3.52cm to 5.20 cm.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Pule sharbatti, Balaji, Sai sharbatti varieties were round in shape whereas Kagzi lime, Vikram, Pramalini varieties were in oval shape. Similar observations were made by Yadlod et al (2018) [12] who noticed oval and round shaped fruits with rough and smooth surface fruits. The length of acid lime fruits was ranging from 4.15cm to 4.64 cm, these findings were in the range of observations were made by Tirthakar et al (2004) [11] ranging between 3.52cm to 5.20 cm.…”
Section: Resultssupporting
confidence: 89%
“…The fruit breadth varied significantly among the selected varieties which breadth ranged between 3.99cm to 4.23cm. These findings were in the range of Yadlod et al (2018) [12] who noticed breadth of fruit ranging from 3.70 to 4.70 cm. Weight of fruit varied significantly among the acid lime varieties.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar findings for the variation in growth parameters were reported by Singh et al (2010), Paithankar et al, (2018) and, Yadlod et al, (2018) who observed similar variation in tree size (tree height and canopy volume) among twenty eight strains of Kagzi lime. Table (3) and Fig.1 show the variations in leaf characters between Mexican lime and the new strain.…”
Section: Morphological Characterization Tree Characterssupporting
confidence: 89%
“…It is difficult to distinguish among citrus cultivars by using morphological traits because citrus trees usually do not bear fruits until three to four years after planting. So apart from morphological characterization, it is desirable to develop alternative methods which are rapid, reliable and more or less not influenced by environment (Paithankar, et al, 2018 andYadlod, et al, 2018). During the past few years, new strategies based on molecular markers have been proposed by numerous investigators to decrease time and power ( Laxman ,2009).…”
Section: Introductionmentioning
confidence: 99%